A Comparison of Factors Influencing the Job Satisfaction among Academic Members of the University of Technology and the University of Science in Vietnam - Duong, Minh-Quang (EDUCARE, 2014)
ABSTRACT: Since the late 1950s, a number of researchers have theorized about the nature of job satisfaction and developed models which attempt to explain differences of job satisfaction. Job satisfaction is a major concern of managers in business, executives in industry, and teachers and administration in educational organization. It is clear that very little research on university faculty job satisfaction has come from the developing world like Vietnam. This aim of this study was to determine the specific factors that affected the job satisfaction of academic members both universities. The study used a questionnaire to survey with 141 academic members from two public universities of Ho Chi Minh City in Vietnam which selected as a statistical sample. The study showed that academic members of two universities were only a moderate level of job satisfaction. However, faculty members in the University of Technology were more satisfied than faculty members in the University of Science. The present analysis found that no significant differences existed job satisfaction of academic members among the two universities; but, there were significant difference between male and female faculty. In addition, male faculty members were generally more satisfied than female colleagues. The study also recognized that job satisfaction of academic members were significantly affected by their work time and institutional characteristics. KEY WORDS: Job satisfaction, Vietnamese higher education, academic members, work time, institutional characteristics, and developing country.About the Author: Minh-Quang Duong is a Lecturer at the Faculty of Education, University of Social Sciences and Humanities VNU-HCMC (Vietnam National University â Ho Chi Minh City), 10-12 Dinh Tien Hoang Road, District 1, Ho Chi Minh City, Vietnam. E-mail: mqduong.ussh@yahoo.comHow to cite this article? Duong, Minh-Quang. (2014). âA Comparison of Factors Influencing the Job Satisfaction among Academic Members of the University of Technology and the University of Science in Vietnamâ in EDUCARE: International Journal for Educational Studies, Vol.6(2) February, pp.169-178. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 4, 2013); Revised (January 8, 2014); and Published (February 17, 2014).Â  Â